Post stroke psychiatric syndrome: a clinical study - Singh, Amrendra K.; Raghuvanshi, Gyanendra (International Journal of Research in Medical Sciences, 2020)
Background: Various psychiatric symptoms are seen after strokes which are usually deserted due to poor familiarity about it, hence better knowledge and understanding of various post stroke psychiatric manifestations may help in early identification and management of it. The aim of present research is to study the demographic and clinical profile of various post stroke psychiatric manifestations. Methods: The study was conducted on ninety patients developing psychiatric symptoms after stroke. Detailed socio-demographic characteristics, clinical profile along with psychiatric assessment were recorded in proforma specially designed for the study. Results: Bulk of this post- stroke psychiatric subjects (45%) was in the age range of 61-80 years of which male and female were 29% and 16% respectively. Most of patients (90%) were residing at rural areas. 47.8 % patients were belonging to lower middle socio-economic status. Majority of subjects (42.8%) were unemployed followed by farmer and skilled worker (20% each), and most of the patients were right handed (97.8%). On clinical parameters maximum subjects (52.2) developed post stroke major depression followed by depression mixed with anxiety (16.6%). Rest of patients suffered from organic anxiety disorder (8.8%), vascular dementia (10%), amnestic syndrome (5.5%), post stroke psychosis (3.3%), organic manic disorder (2.2%), pathological laughter and crying (1.1%). Conclusions: Huge number of patients (52.9%) developed psychiatric problems of diverse nature among patients with stroke syndrome. depression was most common post stroke psychiatric manifestation, followed by mixed anxiety with depression. Generally the post stroke psychiatric manifestations are unrecognized and untreated, which has adverse impact on process of stroke rehabilitation. Thus a detailed psychiatric evaluation is mandatory in all patients of stroke syndrome to rule out psychiatric illness.